Establishing The Total Quality Of A Type Of Result Obtained By An Economic Company - Generalities - Dobrițoiu, Nicolae (Archives of Business Research, 2018)
The results of the activities carried out in an economic company are concretized in one or more types of products or services of a certain quality. The quality of products and services of an organization is determined by the ability to satisfy customers and the intended and unintentional impact on relevant stakeholders, or The quality of products and services not only includes their intended functions and performance but also the value and benefit perceived by the client (SR EN ISO 9000: 2015) According to these definitions, taken from the quality standard SR EN ISO 9000: 2015, it results that a product is of high quality when the following is achieved: -satisfaction of a large number of consumer expectations; -encourage consumers to meet new expectations; -the cost of meeting these expectations should be as small as possible; -the period in which a product meets the expectations must be as high as possible; -the cost of using the product by consumers must be as small as possible.